Left Ventricular Diastolic Dysfunction and E/E′ Ratio as the Strongest Echocardiographic Predictors of Reduced Exercise Capacity After Acute Myocardial Infarction. Issue 4 (23rd February 2015) - Fontes‐Carvalho, Ricardo; Sampaio, Francisco; Teixeira, Madalena; Rocha‐Gonçalves, Francisco; Gama, Vasco; Azevedo, Ana; Leite‐Moreira, Adelino
Abstract Background The mechanisms that determine reduced exercise capacity after acute myocardial infarction (AMI) are not fully understood, especially the relative role of left ventricular diastolic and systolic function. Hypothesis To evaluate the role of different diastolic and systolic function echocardiographic parameters as predictors of reduced functional capacity in patients after AMI. Methods One month after AMI, 225 patients (84% male; mean age, 55.1 ± 10.9 years) were enrolled and underwent detailed echocardiography and cardiopulmonary exercise test on the same day. Systolic and diastolic function was evaluated by echocardiography according to the latest consensus recommendations, including tissue Doppler evaluation. Exercise capacity was evaluated with peak oxygen consumption (VO2). Results Peak VO2 was significantly correlated with early diastolic tissue Doppler velocity (E′) septal (r = 0.42, P < 0.001), E′ lateral (r = 0.35, P < 0.001), septal E/E′ ratio (r = −0.35, P = 0.001), and lateral E/E′ (r = −0.27, P < 0.001). These diastolic function parameters predicted impaired exercise capacity (VO2 <19 mL/kg/min), with an area under the receiver operating characteristic curve of 0.77 (95% confidence interval [CI]: 0.68–0.86, P < 0.001) for septal E/E′. On multivariate analysis, for each unit increase in septal E/E′ ratio there was a −0.35 (95% CI: −0.54 to −0.15) mL/kg/min decrease in peak VO2 independently of age, sex, body mass index, hypertension, and diabetes. There was a mild correlation between peak VO2 and systolic function parameters (r = 0.17, P = 0.01 with ejection fraction; and r = 0.23, P = 0.02 with lateral systolic tissue Doppler velocity) that persisted after multivariate adjustment. Conclusions After AMI, resting diastolic function parameters were the strongest correlates of exercise tolerance. Septal E/E′ ratio was the best echocardiographic predictor of reduced functional capacity.